PENGARUH IMPLEMENTASI PANCA YAMA BRATHA DALAM PELAYANAN PUBLIK TERHADAP KINERJA KARYAWAN LEMBAGA PERKREDITAN DESA DI KECAMATAN PENEBEL - NGURAH MADE NOVIANHA PYNATIH; RAI ARTINI (Universitas Mahasaraswati K. Mataram, 2024)
The aim of this study is to explore the impact of Panca Yama Bratha (ahimsa, satya, asteya, brahmacharya, and awyawaharika) on the performance of employees at LPD in Penebel District. This research was conducted at the LPD located in Penebel District, Tabanan Regency. The subjects of the study include ahimsa, satya, asteya, brahmacharya, awyawaharika, and the performance of LPD employees in the area. The sample size used in this study consists of 70 respondents, employing a survey method. The data analysis technique used is Multiple Linear Regression Analysis. The results indicate that all independent variable namely ahimsa, satya, asteya, brahmacharya, and awyawaharika have a positive and significant partial effect on the performance of LPD employees in Penebel District. Additionally, the overall implementation of Panca Yama Bratha also shows a significant impact on the performance of LPD employees in the region.